Serum antibody fingerprinting of SARS-CoV-2 variants in infected and vaccinated subjects by label-free microarray biosensor - Carzaniga, Thomas; Casiraghi, Luca; Nava, Giovanni; Zanchetta, Giuliano; Inzani, Tommaso; Chiari, Marcella; Bollati, Valentina; Epis, Sara; Bandi, Claudio; Lai, Alessia; Zehender, Gianguglielmo; Bellini, Tommaso; et al. (Frontiers in Immunology, 2024)
Both viral infection and vaccination affect the antibody repertoire of a person. Here we demonstrate that the analysis of serum antibodies carries information not only on the virus type that caused the infection, but also on the specific virus variant. We developed a rapid multiplex assay providing a fingerprint of serum antibodies against five different SARS-CoV-2 variants, based on a microarray of virus antigens immobilized on the surface of a label-free reflectometric biosensor. We analyzed serum from plasma of convalescent subjects and vaccinated volunteers and extracted individual antibody profiles of both total immunoglobulin Ig and IgA fraction. We found that Ig level profiles were strongly correlated with the specific variant of infection or vaccination and that vaccinated subjects displayed larger quantity of total Ig and lower fraction of IgA relative to the population of convalescent unvaccinated subjects.